Bagua and Peru: Extractivism, patriarchal domination and communality - Ortiz Fernández, Carolina (2018)
Ponder over the codes, social and emotional relationship that emerge from the discursive enunciation and acts of the and social actors involved in the socio-environmental conflict occurred in Bagua on June 5, 2009, regarding with classical social theory and the theory of the coloniality of power, on one hand, let us understand other gaze of the society and life from the perspective of being “indigenous” and inhabitant at the Amazon in Peru; on the other hand, part of the strategies of re-colonization of the territories of our America, particularly the Amazon, and constitutes a milestone about the model of development imposed. Unlike the authoritarian concentration of power from the government and the “nation state”, communities depicts an intense democracy and reveal the contradictions between community social existence and the “nation state” depicted by the corporations and the overall pattern of power.